2012
DOI: 10.1073/pnas.1115515109
|View full text |Cite
|
Sign up to set email alerts
|

Life motion signals lengthen perceived temporal duration

Abstract: Point-light biological motions, conveying various different attributes of biological entities, have particular spatiotemporal properties that enable them to be processed with remarkable efficiency in the human visual system. Here we demonstrate that such signals automatically lengthen their perceived temporal duration independent of global configuration and without observers' subjective awareness of their biological nature. By using a duration discrimination paradigm, we showed that an upright biological motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 63 publications
4
35
1
Order By: Relevance
“…Consistent with this hypothesis, there is recent evidence that time perception and motor timing are influenced by animacy: The observation of a biological movement performed by other people may bias the timing of a motor act or the judgement of perceived duration of an event (Watanabe 2008;Bove et al 2009;Carrozzo et al 2010;Zago et al 2011b;Mouta et al 2012;Wang and Jiang 2012). In particular, Carrozzo et al (2010) investigated two different timing tasks: (1) button-press responses aimed at intercepting a falling ball and (2) discrimination of the duration of a stationary flash.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Consistent with this hypothesis, there is recent evidence that time perception and motor timing are influenced by animacy: The observation of a biological movement performed by other people may bias the timing of a motor act or the judgement of perceived duration of an event (Watanabe 2008;Bove et al 2009;Carrozzo et al 2010;Zago et al 2011b;Mouta et al 2012;Wang and Jiang 2012). In particular, Carrozzo et al (2010) investigated two different timing tasks: (1) button-press responses aimed at intercepting a falling ball and (2) discrimination of the duration of a stationary flash.…”
Section: Introductionmentioning
confidence: 74%
“…According to one hypothesis, the time base used by the brain to process visual motion is calibrated against the predictions regarding the motion of biological characters when animacy is detected by the observer, while the time base is calibrated against the predictions of motion of passive objects when no animacy is detected (Chang and Troje 2008;Sebanz and Knoblich 2009;Carrozzo et al 2010;Zago et al 2011a, b;Wang and Jiang 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Wittmann, van Wassenhove, Craig & Paulus (2010a) showed that an object moving towards an observer was perceived as longer in duration than the same object that was static or moving away. Wang & Yi Jiang (2012) also observed a subjective temporal dilation in a bisection task when participants were presented with a motion sequence of point-light walker compared to a non-biological motion or a static picture with the same amount of point lights. However, further investigations are also needed to understand the influence of the temporal memories activated during time judgments for body posture pictures.…”
Section: Embodiment Of Timingmentioning
confidence: 96%
“…For example, perceived motion of upright point light walkers is temporally dilated relative to inverted walkers (Wang & Jiang, 2012; see also Gavazzi, Bisio, & Pozzo, 2013). In the present experiments, we examine how movement influences the perceived duration of sensory outcomes of action.…”
mentioning
confidence: 99%